Responses of humpback whales to a changing climate in the Southern Hemisphere: Priorities for research efforts. (23rd September 2020) - Meynecke, Jan‐Olaf; Seyboth, Elisa; De Bie, Jasper; Menzel Barraqueta, Jan‐Lukas; Chama, Abdoulkadri; Prakash Dey, Subhra; Lee, Serena Blyth; Tulloch, Vivitskaia; Vichi, Marcello; Findlay, Ken; Roychoudhury, Alakendra Narayan; Mackey, Brendan
Abstract: Globally, baleen whales were severely depleted by historic whaling. Recovering populations have been observed to alter their behaviour. These changes have been attributed to climate change in some cases and raise concerns over the successful recovery of baleen whale populations. Current data‐driven statistical habitat and behavioural models have proven useful for addressing questions of whale distribution changes within their limitations. Given observed changes in oceanic conditions, a new approach to managing baleen whale population recovery is necessary. Model predictions of future whale movements and distributions under climate change scenarios are vital to enable adequate conservation management. This paper presents a new perspective on understanding the impacts of climate change on humpback whales, arguing the need for a system‐based multidisciplinary research approach. Our approach includes coupled, mechanistic models based upon robust ecological principles, and integrates key physical, biogeochemical, biological and ecological modules to address long‐term changes associated with climate change. To illustrate the need for this system‐based multidisciplinary approach, we focus on Southern Hemisphere humpback whales, the recovery of which may be impacted by rapid changes in habitat conditions brought about by anthropogenic climate change.